Genetic Divergence in Landraces of Bangladesh Rice (Oryza sativa L.) - Hosan, SM; Sultana, Nasrin; Iftekharudduala, KM; Ahmed, Md Nasar Uddin; Mia, Shamim (The Agriculturists, 2011)
Twenty rice landraces collected from different ecological regions of Bangladesh were studied to assess the nature and magnitude of genetic divergence among them. Based on twelve characters, the genotypes were grouped into five clusters. No parallel relationship between genetic and geographical divergence was observed. Inter-cluster distances were higher than the intra-cluster distances reflecting wider genetic diversity among the genotypes of different groups. The genotypes under cluster IV showed highest divergence among them as it exhibited highest intra-cluster distance. High level of inter-cluster distance was found between cluster II and V and between cluster I and III. Number of filled grains number /panicle, number of panicles/plant, biomass index and grain yield contributed considerably towards total divergence. Germplasm having these characters in the genetically distant cluster could, therefore, offer a significant scope for the development of high yielder through judicious selection. Keywords: Genetic divergence; cluster; landrace; rice (Oryza sativa L.) DOI: 10.3329/agric.v8i2.7574 The Agriculturists 8(2): 28-34 (2010)